Institutions, development, and economic growth - Eicher, Theo S.; García-Peñalosa, Cecilia (CESifo seminar series., 2006)
Annotation The determinants of economic growth and development are hotly debated among economists. Financial crises and failed transition experiments have highlighted the fact that functioning institutions are fundamental to the goal of achieving economic growth. The growth literature has seen an abundance of empirical studies on the influence of institutions and the mechanisms by which institutions affect development. This CESifo volume provides a systematic overview of the current scholarship on the impact of institutions on growth. The contributors, all internationally prominent economists, consider theoretical and empirical relationships between institutions and growth. Concepts covered include "appropriate institutions" (the idea that different institutional arrangements are appropriate at different stages of economic development); liberalized credit markets; the influence of institutions on productivity; institutional and regulatory reforms in the OECD; how innovation and entrepreneurship influence growth (including an analysis of patent activity in the United States from 1790 to 1930); the endogeneity of institutions as seen in the recruitment of elites by higher education institutions; the effect of economic development on transitions to democracy; and technology adoption in agriculture. Contributors:Philippe Aghion, Costas Azariadis, Elise S. Brezis, Matteo Cervellati, François Crouzet, David de la Croix, Theo S. Eicher, Piergiuseppe Fortunato, Cecilia García-Peñalosa, Thorvaldur Gylfason, Murat Iyigun, B. Zorina Khan, Giuseppe Nicoletti, Dani Rodrik, Stefano Scarpetta, Kenneth L. Sokoloff, Uwe Sunde, Utku Teksoz, Gylfi Zoega.